2003
DOI: 10.1095/biolreprod.102.005215
|View full text |Cite
|
Sign up to set email alerts
|

Nonhuman Primate Models of Menopause Workshop1

Abstract: The Nonhuman Primate Models of Menopause Workshop was held on the National Institutes of Health campus in January 2001. The purpose of this workshop, sponsored by the National Institute on Aging, was to review what is known about the female reproductive aging process in various species of monkeys (particularly rhesus, baboons, cynomolgus, and chimpanzees), including hormone profiles during the menopausal transition, occurrence of hot flashes, extent of age-related and menopause-associated changes in hormone le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 69 publications
1
83
0
Order By: Relevance
“…The circulating concentration of testosterone and its pulsatile release decline with age in male rhesus monkeys (37). Rhesus females experience the perimenopausal transition similar to women at similar stages of the life-span, but the age of initiation of endocrine changes varies in both species (38,39). As the perimenopausal transition progresses in women, gonadotropin levels increase.…”
Section: Aging Parallelsmentioning
confidence: 99%
“…The circulating concentration of testosterone and its pulsatile release decline with age in male rhesus monkeys (37). Rhesus females experience the perimenopausal transition similar to women at similar stages of the life-span, but the age of initiation of endocrine changes varies in both species (38,39). As the perimenopausal transition progresses in women, gonadotropin levels increase.…”
Section: Aging Parallelsmentioning
confidence: 99%
“…While the bonobo was menopausal, the two chimpanzees showed evidence of continued ovulation, albeit in an altered, perimenopause-like pattern. When findings of a workshop convened by the National Institute on Aging (NIA) were published more than two decades later, these two studies, comprising a total of 12 old chimpanzees, were found to be the only reports on chimpanzee menopause (Bellino and Wise 2003). The authors summarized the state of knowledge at that time by concluding that menstrual cycles continue until the end of natural life in this ape.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while rhesus monkeys experience similar reproductive changes as women, there is a significant difference in the timing of these events (Bellino & Wise 2002), which might, in part, stem from the seasonal breeding pattern of rhesus monkeys. Indeed, Shideler et al (2001) monitored rhesus monkeys for a complete year and found that menstrual cycling in older females frequently ceased during the nonbreeding season.…”
Section: Introductionmentioning
confidence: 99%